2008
DOI: 10.1891/1540-4153.6.3.122
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American Mothers' Health Practices for Febrile Children

Abstract: The purpose of this study was to identify the health care practices that Mexican American mothers use for children with fever. Surveys ( N = 47) indicated the following common practices: (a) giving acetaminophen (85%), (b) removing warm clothes (66%), and (c) giving ibuprofen (53%). Potentially harmful practices of administering aspirin to children with fever (23%) and placing alcohol on the body (29%) occurred. Other remedies included praying, giving cold baths, giving Vaporub, offering tea to drink, placing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Cough medicine and laxatives were also used for cough and stomach-related symptoms (Mendelson, 2003;Mikhail, 1994). Parents in four studies reported giving their children medications from Mexico (Foronda & Waite, 2008;Grigg et al, 2013;Harrison & Scarinci, 2007;Mikhail, 1994). Reasons for this practice included the high cost of medications in the United States and the availability of antibiotics over the counter in Latin American countries (Grigg et al, 2013;Harrison & Scarinci, 2007).…”
Section: Popular Sector: Self-management Of Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Cough medicine and laxatives were also used for cough and stomach-related symptoms (Mendelson, 2003;Mikhail, 1994). Parents in four studies reported giving their children medications from Mexico (Foronda & Waite, 2008;Grigg et al, 2013;Harrison & Scarinci, 2007;Mikhail, 1994). Reasons for this practice included the high cost of medications in the United States and the availability of antibiotics over the counter in Latin American countries (Grigg et al, 2013;Harrison & Scarinci, 2007).…”
Section: Popular Sector: Self-management Of Illnessmentioning
confidence: 99%
“…Reasons for this practice included the high cost of medications in the United States and the availability of antibiotics over the counter in Latin American countries (Grigg et al, 2013;Harrison & Scarinci, 2007). Three studies reported the use of aspirin for fever, with one noting 23% of mothers using aspirin (Foronda & Waite, 2008;Mikhail, 1994;Taveras et al, 2004). Parents also gave medications bought from pharmacies in Mexican stores primarily because no appointment or permission was needed (Harrison & Scarinci, 2007).…”
Section: Popular Sector: Self-management Of Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies demonstrated consistent themes of fears and deficient or limited maternal knowledge (Berg et al, 2007;Robledo et al, 1999). These studies are also consistent with mother's health practices of febrile children where unsafe fever management was found because of a lack of mother's knowledge (Foronda & Waite, 2008). Rehm (1999) investigated the meaning of religious faith with Mexican American parents, primarily mothers, with a child with chronic health conditions.…”
Section: Familism Collectivism and Biculturalism The Emphasis On Fmentioning
confidence: 57%
“…The significance of the limited studies highlights the potentially often covert practices of home or folk remedies that might not be shared with the health care providers (Bearison, Minian, & Granowetter, 2002;Foronda & Waite, 2008). Gaining an understanding of cultural health beliefs and practices might provide insight into the family's approach to care for their child with CF and carrying out prescribed therapies.…”
Section: Hispanic Mothers' Health Beliefsmentioning
confidence: 99%